A Review of Immune Blockade Safety and Antitumor Activity of Dostarlimab Therapy in Endometrial Cancer - , Purabi Saha; Ajay Kumar; Jyotiprakash Bhanja; Rahaman Shaik; Akash Limba Kawale; Roshan Kumar (International Journal for Research in Applied Sciences and Biotechnology, 2022)
Endometrial cancer is the most prevalent form of gynecologic cancer in the United States, and the annual incidence rates are only expected to continue rising. The majority of women arrive with symptoms that are early in the illness's progression; nevertheless, severe disease bears a far more dire prognosis. As a direct consequence of this, new therapeutic approaches are now being researched for the purpose of treating endometrial cancer. These advancements include a greater knowledge of the genetic underpinnings around the development of endometrial cancer, new molecular targets for the therapy of this illness, and newer surgical approaches. This review is an analysis of the published research on the various developments of endometrial cancer.